Tourism Development of Ciwaluh Ecotourism Village in Watesjaya Village Cigombong Bogor District: - Andika, Adi; Nisa, Karimatun; Sudarijati, Sudarijati; Didi, Didi; Hidayah, Asshafa Dwia Nurul; Maspupah, Siti; Putri, Adistiasari Kencana (Jurnal Pengabdian Masyarakat Formosa, 2023)
Local potential-oriented tourism development is important for increasing income and welfare. In addition to increasing income, this development also aims to attract tourists to visit by enjoying everything that is served and providing comfort and safety at tourist sites. However, Ciwaluh Tourism Village is still low in the application of safety in tourist attractions. Tourism development through this Thematic KKN program is carried out with steps consisting of preparation, implementation and evaluation of activities. The program to be implemented in this activity is the making of warning boards, making rental permit boards, making trash bins and making financial reports. Activities have been realized with outputs in the form of warning boards, rental permit boards, trash bins and books for recording financial reports.